Re: Predictors of infectious complications after targeted prophylaxis for prostate needle biopsy - Miah,S; Winkler,M; Ahmed,HU (European Urology, 2018)
Papagiannopoulos D, Abern M, Wilson N, et alJ Urol 2018;199:155–60Experts’ summary:Papagiannopoulos et al [1] are to be congratulated on their reporting of over 5000 men undergoing transrectal ultrasound-guided (TRUS) prostate biopsy with targeted antimicrobial prophylaxis with preprocedure rectal swab cultures. This method led to an overall infectious complication rate of 1.1%, whilst it was 3.9% for those harbouring a fluoroquinolone-resistant organism (odds ratio 9.98). Their article concluded that one should consider using alternative biopsy approaches to minimise infectious complications in this higher-risk cohort who harbour fluoroquinolone resistance.